The Use of English, Russian and Tatar Etiquette Words and Expressions in Speech Situations of Greeting and Farewell - Khairullina, Dinara (Journal of History Culture and Art Research, 2020)
In the epoch of intercultural communication, professional foreign language proficiency and a high level of communicants’ competence are of great significance. One of the aspects of communicative competence is the possession of skills of speech etiquette formulae application. In the present paper, the author compares some etiquette forms in English, Russian, and Tatar and discusses the use of etiquette formulae expressed in words and phrases corresponding to different communicative situations. The author came to the conclusion that despite the fact that communicative situations are universal, people’s verbal behavior is characterized by national and cultural peculiarities. The choice of etiquette formulae may be conditioned by factors of demographic nature, contextual details, exact words of the actual conversations, habits, traditions, etc. The main communicative and relevant features of the Russian and Tatar languages are special attention and interest in the interlocutor, broad awareness, sincerity, and excessive curiosity. Relevant property of the English communication is individualism, non-interference to others’ affairs, observance of privacy, positiveness, and phatic communication. British verbosity is merely a politeness strategy, that is, a demonstration of respect and attention to others, sincerity is not a necessary condition there. The choice of Tatar etiquette words and expressions in speech situations depends on the influence of religion and religious beliefs.